PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KINERJA KEUANGAN DAN LEVERAGE TERHADAP PENGUNGKAPAN EMISI KARBON (STUDI PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - 2020) - Sa'da, Anis Naila (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to examine the effect of firm size, profitability, financial performance and leverage on the disclosure of carbon emissions. The research method used is quantitative with secondary data types. The population in this study is the energy sector companies listed on the Indonesia Stock Exchange for the period 2018